Decreased Right Temporal Activation and Increased Interhemispheric Connectivity in Response to Speech in Preterm Infants at Term-Equivalent Age - Naoi, Nozomi; Fuchino, Yutaka; Shibata, Minoru; Niwa, Fusako; Kawai, Masahiko; Konishi, Yukuo; Okanoya, Kazuo; Myowa-Yamakoshi, Masako (Frontiers in Psychology, 2013)
Preterm infants are at increased risk of language-related problems later in life; however, few studies have examined the effects of preterm birth on cerebral responses to speech at very early developmental stages. This study examined cerebral activation and functional connectivity in response to infant-directed speech (IDS) and adult-directed speech (ADS) in full-term neonates and preterm infants at term-equivalent age using 94-channel near-infrared spectroscopy (NIRS). The results showed that compared with ADS, IDS increased activity in larger brain areas such as the bilateral frontotemporal, temporal, and temporoparietal regions, both in full-term and preterm infants. Preterm infants exhibited decreased activity in response to speech stimuli in the right temporal region compared with full-term infants, although the significance was low. Moreover, preterm infants exhibited increased interhemispheric connectivity compared with full-term controls, especially in the temporal and temporoparietal regions. These differences suggest that preterm infants may follow different developmental trajectories from those born at term owing to differences in intrauterine and extrauterine development.